Snellen iPad App versus Traditional Light-Box Snellen Chart in Distance Visual Acuity - Al-Essa Aiad (Wolters Kluwer Medknow Publications, 2024)
This study aimed to discover distance visual acuity (VA) assessments through the display of the Snellen chart on the iPad tablet. The findings are equivalent to those obtained using the conventional light-box Snellen chart. In this work, the Snellen iPad app and Eye Chart HD iOS app are utilized among the participants in the Ophthalmology Outpatient Department (OPD) for determining VA. A cross-sectional method was used for the examination, which included 100 new patients who were chosen by random selection. The age requirement for new patients was 8 years and up for both genders. Patients with a VA of less than 6/30 were disqualified from the experiment. Two testing modalities are used to measure VA, such as the iPad Mini 2 with the iOS software Eye Chart HD and the classic Snellen light-box chart. The observation revealed that the Snellen iPad app and the classic light-box Snellen chart produced equivalent findings. The classic Snellen chart may have been memorized by participants before their eye examination, undermining the accuracy of the conclusions of the initial testing modality used. Patient-related variables were also identified as confounders. Future studies should adjust the brightness of the iPad Mini 2 and the traditional light-box Snellen chart to make sure that neither experiment modality's brightness affects the accuracy of the findings. Future research should also investigate the use of premium apps, use both devices, and employ a bigger sample size.